Experimental accumulation of microplastics in acorn barnacle Amphibalanus amphitrite and its use in estimating microplastic concentration in coastal waters - Xu, Xiaoyu; Fang, James Kar-Hei; Wong, Chun-Yuen; Cheung, Siu-Gin (Frontiers in Marine Science, 2023)
Microplastic (MP) pollution has been an emerging problem in the marine environment over the last few decades. Considering wide-ranging negative impacts of MPs on marine organisms, monitoring MP pollution in marine ecosystems is essential and urgent for developing effective management of the problem. An exposure experiment was conducted to assess the potential of the striped barnacle Amphibalanus amphitrite as a bioindicator of MPs. The barnacles were exposed to either polypropylene fibers or fragments for 8 days. A full factorial design was used with the form (fragment, fiber) and concentration of MPs (10, 100, and 1000 items L-1) and exposure duration (2, 4, and 8 days) being independent factors. The highest number of MPs in A. amphitrite was 21.04 ± 15.22 fragments g-1 and 17.60 ± 13.8 fibers g¬-1 wet weight recorded after 4 days of exposure, and the MP concentration in the barnacles was positively correlated with the exposure concentration, regardless of the form of MPs. A regression equation relating the MP concentration in the barnacles and that in the water was computed to estimate the MP concentration in the coastal waters of Hong Kong. The predicted values were close to the published data, indicating the potential of A. amphitrite as a bioindicator of MP pollution.